Evaporation boat and manufacturing method thereof
By adding rare earth metal powder to the evaporation boat and spraying the MoSi2 composite coating, the problems of short service life and weak corrosion resistance of the evaporation boat are solved, and the effects of extending service life, reducing cracks and improving corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411944882.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-18
AI Technical Summary
The existing evaporation boat has a short service life and weak corrosion resistance, which leads to problems such as melting pits, cracks and bulging in the aluminum plating process, increasing production costs.
By adding rare earth metal powder to the evaporation boat and spraying the MoSi2 composite coating on the surface, the microstructure and structure are improved, and the high-temperature mechanical properties and corrosion resistance are improved.
It extends the service life of the evaporation boat, reduces the occurrence of melting pits and cracks, improves corrosion resistance and high temperature resistance, and reduces production costs.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of evaporation boat processing, in particular to an evaporation boat and a manufacturing method thereof. Background Art
[0002] The functional current collector is a "sandwich" structure, with an inner layer of a polymer polymer layer (such as PET, PP or PI), and then an aluminum oxide layer is attached to the polymer layer. The oxide layer improves the interface bonding force between the polymer material and the metal layer through mechanical interlocking and chemical bonding, and then aluminum is plated on the oxide layer. According to the different evaporation processes, composite aluminum is divided into single plating and multiple plating. Regardless of these two methods, the evaporation boat is used to heat, melt and evaporate the aluminum wire. As an indispensable device in the aluminum plating process, the evaporation boat is only used to heat the aluminum wire on the surface, but its surface texture and evaporation area have an important influence on the spreading area of the aluminum liquid and the heat mixing uniformity, which is directly related to aluminum splashing, thereby affecting the flatness and holes of the film surface. In addition, the composition of the evaporation boat also has a great influence on its service life. Generally speaking, the composition of the evaporation boat is boron nitride, titanium diboride, aluminum nitride, aluminum oxide, zirconium oxide, silicon carbide, silicon nitride and other metal and non-metal compounds. Most of them are two-component evaporation boats, with low density, less materials, and easy production and processing. However, with the promotion of composite aluminum, problems such as melt pits, cracks, and heat bulging that occur during use have greatly reduced the service life of traditional evaporation boats, which is an important problem in reducing the cost of the evaporation process.
[0003] At present, evaporation boats are indispensable for aluminum plating. They are consumables in the production process and account for a large proportion of production costs. Usually, evaporation boats begin to have melting pits after 10,000 to 20,000 meters of coating. After 20,000 meters, the melting pits become larger and larger, accompanied by the risk of cracks and bulging, which greatly reduces the service life of the evaporation boats. At the same time, as the evaporation boats are used, the boat surface is corroded by the aluminum liquid reaction, resulting in a reduction in the effective evaporation area. Although secondary grinding of the used boats can increase the number of uses, the grinding cost is still very high.
[0004] Therefore, we propose an evaporation boat and a manufacturing method thereof to solve the problems of short service life and weak corrosion resistance of the evaporation boat. Summary of the invention
[0005] The object of the present invention is to provide an evaporation boat and a manufacturing method thereof to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing an evaporation boat, comprising the following steps: Mix BN (boron nitride) powder, TiB2 (titanium diboride) powder and rare earth metal powder, hot press and sinter to form, and cut and grind after cooling to form an evaporation boat; Furthermore, the mass ratio of BN powder, TiB2 powder and rare earth metal powder is (5-9):(1-5):(0.1-0.4).
[0007] Furthermore, the process conditions of hot pressing sintering are: temperature 1500-1700°C, pressure 15-30MPa; The cooling temperature is 20-30℃.
[0008] Furthermore, the rare earth metal powder is a mixture of one or more of Y2O3 (yttrium oxide), CeO2 (cerium oxide), La2O3 (lanthanum oxide), and Ln2O3 (indium oxide).
[0009] Further, BN powder: CAS number 10043-11-5, 1000 mesh, sourced from Liaoning Borda Technology Co., Ltd.; TiB2 powder: CAS number 12045-63-5, 0.5-1μm, from Yumu (Ningbo) New Materials Co., Ltd. Y2O3 powder: CAS number 1314-36-9, 3.0-6.0μm, from Ganzhou Jiayuan New Materials Co., Ltd. CeO2 powder: CAS number 1306-38-3, 325 mesh, from Beijing Yanxi New Material Technology Co., Ltd.; La2O3 powder: CAS number 1312-81-8, 80 mesh, from Ganzhou Tejing New Material Technology Co., Ltd.; Ln2O3 powder: CAS number is 1312-43-2, purity is 99%, and it comes from Shandong Desheng New Materials Co., Ltd.
[0010] In the above technical scheme, rare earth metals are added to the evaporation boat to improve the microstructure and organization of the evaporation boat, and to improve the high-temperature mechanical properties, elastic modulus and fracture energy of the evaporation boat, thereby alleviating the process of the appearance of the molten pit, reducing the probability of surface cracks and bulging, and extending the service life of the evaporation boat.
[0011] Furthermore, the surface of the evaporation boat is also provided with a coating, and the preparation process is as follows: The obtained evaporation boat is ultrasonically cleaned, and a layer of alloy powder is firstly sprayed on the surface thereof, and then a MoSi2 composite powder is sprayed on the surface thereof to form a coating.
[0012] Furthermore, the process conditions of ultrasonic cleaning are: power 300-800W, time 0.5-1.5h.
[0013] Furthermore, the alloy powder is NiCrAlY powder (nickel-chromium-aluminum-yttrium alloy powder), 325 mesh, sourced from Qinghe County Ruijiang Metal Materials Co., Ltd.
[0014] Furthermore, the coating is a MoSi2 composite coating, which is prepared by the following process: Mullite whisker, MoSi2 powder and Al2O3 powder are mixed and ball-milled to obtain a mixed powder. Polyvinyl alcohol is added to the mixed powder, ball-milled and spray-granulated to obtain MoSi2 composite powder. The powder is sprayed on the surface of an evaporation boat using plasma spraying technology to form a MoSi2 composite coating.
[0015] Further, the molar ratio of mullite whisker, MoSi2 powder and Al2O3 powder is (0.5-2):(6-9):(1-4); The volume ratio of the mixed powder and polyvinyl alcohol is (7.5-9): (1-2.5).
[0016] Furthermore, polyvinyl alcohol is added in the form of a solution with a mass fraction of 2-3%.
[0017] Furthermore, the process conditions of ball milling are: rotation speed 280-380r / min, time 0.5-2h.
[0018] Furthermore, the process conditions of spray granulation are: inlet temperature 130-160°C, outlet temperature 50-80°C, feed rate 16-20mL / min, air flow rate 0.4-0.7m / min, nitrogen flow rate 0.03-0.06m / min, and nozzle pressure 0.07-0.1MPa.
[0019] Furthermore, the process conditions of plasma spraying are: inlet temperature 190-220°C, outlet temperature 80-110°C, atomization speed 13000-16000rpm, and feed rate 620-650mL / min.
[0020] Further, MoSi2 powder: CAS number 12136-78-6, 1-3 μm, from Nangong Dinghong Metal Materials Co., Ltd.; Al2O3 powder: CAS number is 1344-28-1, 100 mesh, from Hebei Yinbai Alloy Welding Material Co., Ltd.; Polyvinyl alcohol: CAS number is 9002-89-5, viscosity is 21.0-29.0cps, sourced from Jinan Quanxing New Materials Co., Ltd.
[0021] In the above technical scheme, when mullite whiskers are mixed with the coating, a three-dimensional network structure can be formed between Al2O3, which can improve the strength of the coating without reducing the porosity of the coating, and effectively prevent the generation and expansion of cracks in the evaporation boat; mullite whiskers have a small thermal expansion coefficient and good high temperature resistance, which can increase the service life of the evaporation boat at high temperatures; mullite whiskers do not react chemically with metals and have good corrosion resistance. Mixing with the coating can enhance the corrosion resistance of the coating and slow down the corrosion rate of the evaporation boat; in addition, mullite whiskers also have a toughening effect, and their high strength and high rigidity can effectively transfer loads, disperse stress, and improve the overall strength and toughness of the coating.
[0022] Furthermore, the specific preparation process of the mullite whisker is as follows: The kaolin, aluminum fluoride and sodium sulfate are mixed, ball-milled, dried, calcined, cooled, ground and washed to obtain mullite whiskers.
[0023] Furthermore, the mass ratio of kaolin, aluminum fluoride and sodium sulfate is (4-6): (0.5-2): (4-6).
[0024] Furthermore, the process conditions of ball milling are: speed 280-380r / min, time 0.5-2h; The drying temperature is 50-60℃.
[0025] Furthermore, the calcination process conditions are: heating from 25-30°C to 1200-1300°C at a heating rate of 3-5°C / min, and keeping the temperature for 1-3h; The cooling temperature is 20-25℃.
[0026] Further, kaolin: 1250 mesh, model S36210, sourced from Shanghai Yuanjiang Chemical Co., Ltd.; Aluminum fluoride: CAS number is 7784-18-1, 80-120 mesh, from Changshu Hongjia Fluoride Technology Co., Ltd. Sodium sulfate: CAS number is 7757-82-6, 99 mesh, sourced from Huaian Haoda Trading Co., Ltd.
[0027] In the above technical scheme, low-cost kaolin is used as raw material, which has high economic benefits. Aluminum fluoride volatilizes fluorine during the heating process, providing a favorable gas phase environment for whisker growth and promoting the growth of mullite whiskers. Sodium sulfate has a low melting point and provides a liquid phase environment for the growth of mullite whiskers during the reaction.
[0028] Compared with the prior art, the present invention has the following beneficial effects: 1. By adding rare earth metals into the evaporation boat, the microstructure and organization of the evaporation boat are improved, and the high-temperature mechanical properties, elastic modulus and fracture energy of the evaporation boat are improved, thereby alleviating the process of the appearance of the molten pit, reducing the probability of surface cracks and bulging, and extending the service life of the evaporation boat.
[0029] 2. By mixing mullite whiskers with the coating, a three-dimensional network structure is formed between Al2O3, which can improve the strength of the coating without reducing the porosity of the coating, and effectively prevent the generation and expansion of cracks in the evaporation boat; the high strength and high rigidity of mullite whiskers can effectively transfer loads, disperse stress, and improve the overall strength of the coating; mullite whiskers have a small thermal expansion coefficient and good high temperature resistance, which increases the service life of the evaporation boat at high temperatures; in addition, mullite whiskers do not react chemically with metals and have good corrosion resistance. Mixing with the coating can enhance the corrosion resistance of the coating and slow down the corrosion rate of the evaporation boat.
[0030] 3. Using low-priced kaolin as raw material has high economic benefits. Aluminum fluoride volatilizes fluorine during the heating process, providing a favorable gas phase environment for whisker growth and promoting the growth of mullite whiskers. Sodium sulfate has a low melting point and provides a liquid phase environment for the growth of mullite whiskers during the reaction. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] In the following specific implementations, BN powder: CAS number is 10043-11-5, 1000 mesh, from Liaoning Borda Technology Co., Ltd.; TiB2 powder: CAS number 12045-63-5, 0.5-1μm, from Yumu (Ningbo) New Materials Co., Ltd. Y2O3 powder: CAS number 1314-36-9, 3.0-6.0μm, from Ganzhou Jiayuan New Materials Co., Ltd. CeO2 powder: CAS number 1306-38-3, 325 mesh, from Beijing Yanxi New Material Technology Co., Ltd.; La2O3 powder: CAS number 1312-81-8, 80 mesh, from Ganzhou Tejing New Material Technology Co., Ltd.; Ln2O3 powder: CAS number is 1312-43-2, purity is 99%, from Shandong Desheng New Materials Co., Ltd.; The alloy powder is NiCrAlY powder (nickel-chromium-aluminum-yttrium alloy powder), 325 mesh, from Qinghe County Ruijiang Metal Materials Co., Ltd.; MoSi2 powder: CAS number 12136-78-6, 1-3 μm, from Nangong Dinghong Metal Materials Co., Ltd. Al2O3 powder: CAS number is 1344-28-1, 100 mesh, from Hebei Yinbai Alloy Welding Material Co., Ltd.; Polyvinyl alcohol: CAS number is 9002-89-5, viscosity is 21.0-29.0cps, from Jinan Quanxing New Materials Co., Ltd. Kaolin: 1250 mesh, model S36210, from Shanghai Yuanjiang Chemical Co., Ltd.; Aluminum fluoride: CAS number is 7784-18-1, 80-120 mesh, from Changshu Hongjia Fluoride Technology Co., Ltd. Sodium sulfate: CAS number is 7757-82-6, 99 mesh, sourced from Huaian Haoda Trading Co., Ltd.
[0033] Example 1: A process for preparing an evaporation boat, comprising the following process: BN powder, TiB2 powder and Y2O3 powder are mixed, hot-pressed and sintered, and then cut and polished after cooling to form an evaporation boat; the mass ratio of BN powder, TiB2 powder and Y2O3 powder is 9:1:0.1; the process conditions of hot-pressing and sintering are: temperature 1700°C, pressure 30MPa.
[0034] Example 2: A process for preparing an evaporation boat, comprising the following process: BN powder, TiB2 powder and Y2O3 powder are mixed, hot-pressed and sintered, and then cut and polished after cooling to form an evaporation boat; the mass ratio of BN powder, TiB2 powder and Y2O3 powder is 7:3:0.2; the process conditions of hot-pressing and sintering are: temperature 1600°C, pressure 20MPa.
[0035] Embodiment 3: A process for preparing an evaporation boat, comprising the following process: BN powder, TiB2 powder and Y2O3 powder are mixed, hot-pressed and sintered, and then cut and polished after cooling to form an evaporation boat; the mass ratio of BN powder, TiB2 powder and Y2O3 powder is 5:5:0.4; the process conditions of hot-pressing and sintering are: temperature 1500°C, pressure 15MPa.
[0036] Example 4: A process for preparing an evaporation boat, comprising the following process: BN powder, TiB2 powder and CeO2 powder are mixed, hot-pressed and sintered into shape, and then cut and polished after cooling to form an evaporation boat; the mass ratio of BN powder, TiB2 powder and CeO2 powder is 9:1:0.1; the process conditions for hot-pressing and sintering are: temperature 1700°C, pressure 30MPa.
[0037] Example 5: A process for preparing an evaporation boat, comprising the following process: BN powder, TiB2 powder and CeO2 powder are mixed, hot-pressed and sintered into shape, and then cut and polished after cooling to form an evaporation boat; the mass ratio of BN powder, TiB2 powder and CeO2 powder is 7:3:0.2; the process conditions of hot-pressing and sintering are: temperature 1600°C, pressure 20MPa.
[0038] Example 6: A process for preparing an evaporation boat, comprising the following process: BN powder, TiB2 powder and CeO2 powder are mixed, hot-pressed and sintered into shape, and then cut and polished after cooling to form an evaporation boat; the mass ratio of BN powder, TiB2 powder and CeO2 powder is 5:5:0.4; the process conditions of hot-pressing and sintering are: temperature 1500°C, pressure 15MPa.
[0039] Example 7: A process for preparing an evaporation boat, comprising the following process: BN powder, TiB2 powder and La2O3 powder are mixed, hot-pressed and sintered, and then cut and polished after cooling to form an evaporation boat; the mass ratio of BN powder, TiB2 powder and La2O3 powder is 9:1:0.1; the process conditions of hot-pressing and sintering are: temperature 1700°C, pressure 30MPa.
[0040] Embodiment 8: A process for preparing an evaporation boat, comprising the following process: BN powder, TiB2 powder and La2O3 powder are mixed, hot-pressed and sintered, and then cut and polished after cooling to form an evaporation boat; the mass ratio of BN powder, TiB2 powder and La2O3 powder is 7:3:0.2; the process conditions of hot-pressing and sintering are: temperature 1600°C, pressure 20MPa.
[0041] Example 9: A process for preparing an evaporation boat, comprising the following process: BN powder, TiB2 powder and La2O3 powder are mixed, hot-pressed and sintered, and then cut and polished after cooling to form an evaporation boat; the mass ratio of BN powder, TiB2 powder and La2O3 powder is 5:5:0.4; the process conditions of hot-pressing and sintering are: temperature 1500°C, pressure 15MPa.
[0042] Embodiment 10: A process for preparing an evaporation boat, comprising the following process: BN powder, TiB2 powder, La2O3 powder and Y2O3 powder are mixed, hot-pressed and sintered into shape, and then cut and polished after cooling to form an evaporation boat; the mass ratio of BN powder, TiB2 powder, La2O3 powder and Y2O3 powder is 9:1:0.1:0.1; the process conditions for hot-pressing and sintering are: temperature 1700°C, pressure 30MPa.
[0043] Example 11: A process for preparing an evaporation boat, comprising the following process: BN powder, TiB2 powder, La2O3 powder and Y2O3 powder are mixed, hot-pressed and sintered, and then cut and polished after cooling to form an evaporation boat; the mass ratio of BN powder, TiB2 powder, La2O3 powder and Y2O3 powder is 7:3:0.2:0.2; the process conditions of hot-pressing and sintering are: temperature 1600°C, pressure 20MPa.
[0044] Example 12: A process for preparing an evaporation boat, comprising the following process: BN powder, TiB2 powder, La2O3 powder and Y2O3 powder are mixed, hot-pressed and sintered, and then cut and polished after cooling to form an evaporation boat; the mass ratio of BN powder, TiB2 powder, La2O3 powder and Y2O3 powder is 5:5:0.4:0.4; the process conditions of hot-pressing and sintering are: temperature 1500°C, pressure 15MPa.
[0045] Example 13: A process for preparing an evaporation boat, comprising the following process: BN powder, TiB2 powder, La2O3 powder and Ln2O3 powder are mixed, hot-pressed and sintered, and then cut and polished after cooling to form an evaporation boat; the mass ratio of BN powder, TiB2 powder, La2O3 powder and Ln2O3 powder is 9:1:0.1:0.1; the process conditions of hot-pressing and sintering are: temperature 1700°C, pressure 30MPa.
[0046] Example 14: A process for preparing an evaporation boat, comprising the following process: BN powder, TiB2 powder, La2O3 powder and Ln2O3 powder are mixed, hot-pressed and sintered, and then cut and polished after cooling to form an evaporation boat; the mass ratio of BN powder, TiB2 powder, La2O3 powder and Ln2O3 powder is 7:3:0.2:0.2; the process conditions of hot-pressing and sintering are: temperature 1600°C, pressure 20MPa.
[0047] Example 15: A process for preparing an evaporation boat, comprising the following process: BN powder, TiB2 powder, La2O3 powder and Ln2O3 powder are mixed, hot-pressed and sintered, and then cut and polished after cooling to form an evaporation boat; the mass ratio of BN powder, TiB2 powder, La2O3 powder and Ln2O3 powder is 5:5:0.4:0.4; the process conditions of hot-pressing and sintering are: temperature 1500°C, pressure 15MPa.
[0048] Example 16: A process for preparing an evaporation boat, comprising the following steps: (1) Preparation of mullite whiskers: Kaolin, aluminum fluoride and sodium sulfate were mixed, ball-milled, dried, calcined, cooled, ground and washed to obtain mullite whiskers; the mass ratio of kaolin, aluminum fluoride and sodium sulfate was 6:2:6; the process conditions of ball milling were: speed 380r / min, time 2h; drying temperature was 60℃; the process conditions of calcination were: heating from 30℃ to 1300℃ at a heating rate of 5℃ / min, and keeping warm for 3h; cooling temperature was 25℃; (2) Preparation of coating: Mullite whisker, MoSi2 powder and Al2O3 powder are mixed and ball-milled to obtain a mixed powder, polyvinyl alcohol is added to the mixed powder, ball-milled and spray-granulated to obtain MoSi2 composite powder, and the powder is sprayed on the surface of the evaporation boat by plasma spraying technology to form a MoSi2 composite coating; the molar ratio of mullite whisker, MoSi2 powder and Al2O3 powder is 2:9:4; the volume ratio of mixed powder and polyvinyl alcohol is 9:2.5; the mass fraction of polyvinyl alcohol is 3%; the process conditions of ball milling are: speed 380r / min, time 2h; the process conditions of spray granulation are: inlet temperature 160℃, outlet temperature 80℃, feed speed 20mL / min, air flow rate 0.7m / min, nitrogen flow rate 0.06m / min, nozzle pressure 0.1MPa; the process conditions of plasma spraying are: inlet temperature 220℃, outlet temperature 110℃, atomization speed 16000rpm, feed amount 650mL / min; (3) Preparation of evaporation boat: BN powder, TiB2 powder and Y2O3 powder are mixed, hot-pressed and sintered into shape, and then cut and polished after cooling to form an evaporation boat; the evaporation boat is ultrasonically cleaned, and a layer of alloy powder is first sprayed on its surface, and then MoSi2 composite powder is sprayed to form a coating; the mass ratio of BN powder, TiB2 powder and Y2O3 powder is 9:1:0.1; the process conditions for hot-pressing and sintering are: temperature 1700℃, pressure 30MPa; cooling temperature is 30℃; the process conditions for ultrasonic cleaning are: power 800W, time 1.5h.
[0049] Example 17: A process for preparing an evaporation boat, comprising the following steps: (1) Preparation of mullite whiskers: Kaolin, aluminum fluoride and sodium sulfate were mixed, ball-milled, dried, roasted, cooled, ground and washed to obtain mullite whiskers; the mass ratio of kaolin, aluminum fluoride and sodium sulfate was 5:1:5; the process conditions of ball milling were: speed 300r / min, time 1h; drying temperature was 55℃; the process conditions of roasting were: heating from 27℃ to 1250℃ at a heating rate of 4℃ / min, and keeping warm for 2h; cooling temperature was 22℃; (2) Preparation of coating: Mullite whisker, MoSi2 powder and Al2O3 powder are mixed and ball-milled to obtain a mixed powder, polyvinyl alcohol is added to the mixed powder, ball-milled and spray-granulated to obtain MoSi2 composite powder, and the powder is sprayed on the surface of the evaporation boat by plasma spraying technology to form a MoSi2 composite coating; the molar ratio of mullite whisker, MoSi2 powder and Al2O3 powder is 1:7:3; the volume ratio of mixed powder and polyvinyl alcohol is 8:2; the mass fraction of polyvinyl alcohol is 2.5%; the process conditions of ball milling are: speed 300r / min, time 1h; the process conditions of spray granulation are: inlet temperature 150℃, outlet temperature 60℃, feed speed 17mL / min, air flow rate 0.5m / min, nitrogen flow rate 0.04m / min, nozzle pressure 0.08MPa; the process conditions of plasma spraying are: inlet temperature 200℃, outlet temperature 90℃, atomization speed 14000rpm, feed amount 630mL / min; (3) Preparation of evaporation boat: BN powder, TiB2 powder and Y2O3 powder are mixed, hot-pressed and sintered into shape, and then cut and polished after cooling to form an evaporation boat; the obtained evaporation boat is ultrasonically cleaned, and a layer of alloy powder is first sprayed on its surface, and then MoSi2 composite powder is sprayed to form a coating; the mass ratio of BN powder, TiB2 powder and Y2O3 powder is 7:3:0.2; the process conditions for hot-pressing and sintering are: temperature 1600℃, pressure 20MPa; cooling temperature is 25℃; the process conditions for ultrasonic cleaning are: power 400W, time 1h.
[0050] Example 18: A process for preparing an evaporation boat, comprising the following steps: (1) Preparation of mullite whiskers: Kaolin, aluminum fluoride and sodium sulfate were mixed, ball-milled, dried, calcined, cooled, ground and washed to obtain mullite whiskers; the mass ratio of kaolin, aluminum fluoride and sodium sulfate was 4:0.5:4; the process conditions of ball milling were: speed 280r / min, time 0.5h; drying temperature was 50℃; the process conditions of calcination were: heating from 25℃ to 1200℃ at a heating rate of 3℃ / min, and keeping warm for 1h; cooling temperature was 20℃; (2) Preparation of coating: Mullite whisker, MoSi2 powder and Al2O3 powder are mixed and ball-milled to obtain a mixed powder, polyvinyl alcohol is added to the mixed powder, ball-milled and spray-granulated to obtain MoSi2 composite powder, and the powder is sprayed on the surface of the evaporation boat by plasma spraying technology to form a MoSi2 composite coating; the molar ratio of mullite whisker, MoSi2 powder and Al2O3 powder is 0.5:6:1; the volume ratio of mixed powder and polyvinyl alcohol is 7.5:1; the mass fraction of polyvinyl alcohol is 2%; the process conditions of ball milling are: speed 280r / min, time 0.5h; the process conditions of spray granulation are: inlet temperature 130℃, outlet temperature 50℃, feed speed 16mL / min, air flow rate 0.4m / min, nitrogen flow rate 0.03m / min, nozzle pressure 0.07MPa; the process conditions of plasma spraying are: inlet temperature 190℃, outlet temperature 80℃, atomization speed 13000rpm, feed amount 620mL / min; (3) Preparation of evaporation boat: BN powder, TiB2 powder and Y2O3 powder are mixed, hot-pressed and sintered into shape, and then cut and polished after cooling to form an evaporation boat; the evaporation boat is ultrasonically cleaned, and a layer of alloy powder is first sprayed on its surface, and then MoSi2 composite powder is sprayed to form a coating; the mass ratio of BN powder, TiB2 powder and Y2O3 powder is 5:5:0.4; the process conditions for hot-pressing and sintering are: temperature 1500℃, pressure 15MPa; cooling temperature is 20℃; the process conditions for ultrasonic cleaning are: power 300W, time 0.5h.
[0051] Example 19: Taking Example 16 as an example, Y2O3 powder is replaced with CeO2 powder, and the other steps remain unchanged.
[0052] Example 20: Taking Example 17 as an example, Y2O3 powder is replaced with CeO2 powder, and the other steps remain unchanged.
[0053] Example 21: Taking Example 18 as an example, Y2O3 powder is replaced with CeO2 powder, and the other steps remain unchanged.
[0054] Example 22: Taking Example 16 as an example, Y2O3 powder is replaced with La2O3 powder, and the other steps remain unchanged.
[0055] Example 23: Taking Example 17 as an example, Y2O3 powder is replaced with La2O3 powder, and the other steps remain unchanged.
[0056] Example 24: Taking Example 18 as an example, Y2O3 powder is replaced with La2O3 powder, and the other steps remain unchanged.
[0057] Example 25: Taking Example 16 as an example, the Y2O3 powder is replaced with a mixture of La2O3 powder and Y2O3 powder, and the other steps remain unchanged.
[0058] Example 26: Taking Example 17 as an example, the Y2O3 powder is replaced with a mixture of La2O3 powder and Y2O3 powder, and the other steps remain unchanged.
[0059] Example 27: Taking Example 18 as an example, the Y2O3 powder is replaced with a mixture of La2O3 powder and Y2O3 powder, and the other steps remain unchanged.
[0060] Example 28: Taking Example 16 as an example, the Y2O3 powder is replaced with a mixture of La2O3 powder and Ln2O3 powder, and the other steps remain unchanged.
[0061] Example 29: Taking Example 17 as an example, the Y2O3 powder is replaced with a mixture of La2O3 powder and Ln2O3 powder, and the other steps remain unchanged.
[0062] Example 30: Taking Example 18 as an example, the Y2O3 powder is replaced with a mixture of La2O3 powder and Ln2O3 powder, and the other steps remain unchanged.
[0063] Comparative Example 1: Compared with Example 1, no rare earth metal powder is added during the preparation process, and other conditions remain unchanged. A preparation process of an evaporation boat includes the following steps: BN powder and TiB2 powder are mixed, hot-pressed and sintered into shape, and then cut and polished after cooling to form an evaporation boat; the mass ratio of BN powder to TiB2 powder is 9:1; the process conditions for hot-pressing and sintering are: temperature 1700°C, pressure 30MPa.
[0064] Comparative Example 2: Taking Example 16 as a comparison, no rare earth metal powder is added during the preparation process, no coating is sprayed, and other conditions remain unchanged.
[0065] Experiment: Take the evaporation boat obtained in Examples 1-15 and Comparative Example 1, use it for evaporation aluminum plating, heating temperature 1200°C, wire feeding rate 80mm / min, coating 15000m, take it down to measure the melting pit area, depth and effective evaporation area of aluminum liquid; Melt pit area: Use Image J to calculate the melt pit area, take a photo of the melt pit, import it into the software, and analyze it according to the actual calibrated length; Depth: Use a wire, stand it vertically at the deepest part of the molten pit, mark the position flush with the boat surface, and measure the length; Hardness test: Take the evaporation boats obtained in Example 1, Examples 16-30, and Comparative Example 2, and use a Mohs hardness tester to perform Mohs hardness test on the obtained evaporation boats; Corrosion resistance test: Take the evaporation boats obtained in Example 1, Examples 16-30, and Comparative Example 2, and perform continuous evaporation aluminum plating, and record the average corrosion rate within 12 hours; High temperature resistance test: Take the evaporation boats obtained in Example 1, Examples 16-30, and Comparative Example 2, burn them at 1200°C, and record the time when cracks appear in the evaporation boats;
[0066] Table 1 Test results of melting pit area, depth and effective evaporation area of aluminum liquid of evaporation boat It can be seen from Table 1 that by adding rare earth metal elements during the production process of the evaporation boat, its microstructure and organization can be improved, and the performance can be improved; at the same time, the addition of rare earth elements improves the high-temperature mechanical properties of the evaporation boat, and improves the elastic modulus and fracture energy. By comparing the embodiments and comparative examples, the addition of rare earth elements can reduce the area and depth of the molten pit during the use of the evaporation boat. At the same time, due to the increase in corrosion resistance, the effective evaporation area of the aluminum liquid on the boat surface is retained to be larger, extending the service life of the evaporation boat;
[0067] Table 2 Test results of hardness, corrosion resistance and high temperature resistance of evaporation boat It can be seen from Table 2 that the composite coating increases the hardness, corrosion resistance and high temperature resistance of the evaporation boat. This is because the mullite whiskers in the composite coating form a three-dimensional network structure between Al2O3, which improves the hardness of the coating and thus the hardness of the evaporation boat. The high strength and high rigidity of the mullite whiskers can transfer loads, disperse stress, and improve the overall strength of the coating. The mullite whiskers have a small thermal expansion coefficient and good high temperature resistance, which can increase the service life of the evaporation boat at high temperatures. The mullite whiskers also do not react chemically with metals and have good corrosion resistance. Mixing with the coating can enhance the corrosion resistance of the coating and slow down the corrosion rate of the evaporation boat.
[0068] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A method for manufacturing an evaporation boat, characterized in that: The following steps are involved: BN powder, TiB2 powder and rare earth metal powder are mixed, hot pressed and sintered into shape, and then cut and polished after cooling to form an evaporation boat.
2. The method for manufacturing an evaporation boat according to claim 1, characterized in that: The process conditions of hot pressing sintering are: temperature 1500-1700℃, pressure 15-30MPa.
3. The method for manufacturing an evaporation boat according to claim 1, characterized in that: The mass ratio of BN powder, TiB2 powder and rare earth metal powder is (5-9):(1-5):(0.1-0.4).
4. The method for manufacturing an evaporation boat according to claim 3, characterized in that: The rare earth metal powder is a mixture of one or more of Y2O3, CeO2, La2O3, and Ln2O3.
5. The method for manufacturing an evaporation boat according to claim 1, characterized in that: The surface of the evaporation boat is also provided with a coating, and the preparation process is as follows: The obtained evaporation boat is ultrasonically cleaned, and a layer of alloy powder is firstly sprayed on the surface thereof, and then a MoSi2 composite powder is sprayed on the surface thereof to form a coating.
6. The method for manufacturing an evaporation boat according to claim 5, characterized in that: The coating is a MoSi2 composite coating, which is prepared by the following process: Mullite whisker, MoSi2 powder and Al2O3 powder are mixed and ball-milled to obtain a mixed powder. Polyvinyl alcohol is added to the mixed powder, ball-milled and spray-granulated to obtain MoSi2 composite powder. The powder is sprayed on the surface of an evaporation boat using plasma spraying technology to form a MoSi2 composite coating.
7. The method for manufacturing an evaporation boat according to claim 6, characterized in that: The process conditions of plasma spraying are: inlet temperature 190-220°C, outlet temperature 80-110°C, atomization speed 13000-16000rpm, and feed rate 620-650mL / min.
8. The method for manufacturing an evaporation boat according to claim 6, characterized in that: The mullite whisker is prepared by the following process: The kaolin, aluminum fluoride and sodium sulfate are mixed, ball-milled, dried, calcined, cooled, ground and washed to obtain mullite whiskers.
9. The method for manufacturing an evaporation boat according to claim 8, characterized in that: The calcination process conditions are: heating from 25-30°C to 1200-1300°C at a heating rate of 3-5°C / min, and keeping warm for 1-3h.
10. An evaporation boat, characterized in that: The method is prepared by the preparation process described in any one of claims 1 to 9.